Synthesis and Spectroscopic Characterization of a New Series of Benzo[E][1,3]Oxazepine Compounds from Schiff Bases - Azeez, Hashim J.; Qadir, Kali M. (Science Journal of University of Zakho, 2017)
The present work includes synthesis, characterization and investigation the biological activity of a new series of benzo [e][1, 3]oxazepine compounds which were prepared from Schiff bases. The synthetic routes have been divided into two steps as follows: The first step includes the synthesis of Schiff bases, by treatment of 4-amino diphenyl amine and different substituted benzaldehydes in absolute ethanol using glacial acetic acid as catalyst. The second step of this work is the synthesis of a series benzo [e][1, 3] oxazepine, by the reaction of the synthesized Schiff bases with phthalic anhydride in dry benzene. The structures of the synthesized products were confirmed on the basis of (UV-Visible, FT-IR, 1H-NMR, 13C-NMR spectroscopy. Some of the synthesized compounds were evaluated for antibacterial activity, against two types of bacteria, Staphylococcus aureus (Gram positive) and Pseudomonas aeruginosa (Gram negative).The results showed the high sensitivity of the synthesized compounds to both types of bacteria.